QURAN MEMORIZATION STRATEGY IN PRODUCING HUFFAẒ IN TELUK NIBUNG SUB-DISTRICT, TANJUNG BALAI - Khairuddin, Khairuddin; Budianti, Yusnaili; Zulheddi, Zulheddi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2023)
This study aims to analyze: 1) to describe and analyze how the strategy of the Al-Qur'an Tahfiẓ House in Producing Huffaẓ in Teluk Nibung District, Tanjung Balai; 2) to analyze the obstacles faced by the Al-Qur'an Tahfiẓ House in Producing Huffaẓ in Teluk Nibung District, Tanjung Balai; and 3) to describe how the results of the Al-Qur'an Tahfiẓ House in Producing Huffaẓ in Teluk Nibung District, Tanjung Balai. This study uses a qualitative method. While collecting data, researchers obtained by observation techniques, interviews and study documentation. The data source in this study was obtained from the research location, namely the Al-Qur'an Tahfiẓ House, Teluk Nibung District, Tanjung Balai. Related to the focus of this study are the Deputy Head of Madrasah for Curriculum and Student Affairs, & Facilities and Infrastructure, Teachers and Students at MTs Rumah Tahfiẓ Al-Qur'an, Teluk Nibung District, Tanjung Balai. The analysis used refers to model data. Miles and Huberman. The results of this study are: 1) The strategy of the Al-Qur'an Tahfiẓ House in Producing Huffaẓ in Teluk Nibung District, Tanjung Balai, is the muraja'ah strategy. 2) The obstacles faced by the Al-Qur'an Tahfiẓ House in Teluk Nibung District, Tanjung Balai, stem from two factors, namely a. Internal factors, lack of interest and talent, lack of self-motivation and older age. b. External factors include how the teacher provides guidance and the density of the material that students must learn. 3) The results of this study indicate that the strategy applied is appropriate and requires even stricter guidance from caregivers. The existence of good cooperation between teachers and students makes this strategy work well.